Implementasi Kepemimpinan Transformasional di SDN Sukasari Cirebon - Astia Aprina; Husnurijal; Lia Eliana; Indah Rahmawati; Maya Eliana; Dwi Hastuti; Yiyin Bayinah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the implementation of transformational leadership at SDN Sukasari Cirebon, with the aim of improving teacher performance, staff motivation and parental participation in supporting educational success. The principal plays a strategic role in implementing the four dimensions of transformational leadership: idealistic influence, inspirational motivation, intellectual stimulation and individualized consideration. This approach not only improves discipline and teaching quality but also creates an environment conducive to innovation and collaboration between teachers and staff. Through interviews, observations and document analysis, this study found that transformational leadership has a positive impact on teachers' morale and creativity, parents' active involvement in the education process and improved student learning outcomes. In addition, principals play an important role in facilitating teachers' professional development through training and supervision. Nevertheless, there are some challenges such as lack of teacher discipline and parental involvement that still require further attention. The results show that transformational leadership can be effectively implemented in the context of primary education to drive positive change and improve learning quality sustainably.